Knowledge, Attitude, and Practice Regarding Iron Deficiency Anemia Prevention Among Female Adolescents in Bogor City, Indonesia - Wardani, Riastuti Kusuma; Nurmansyah, Muhammad Iqbal; Yustiyani; Iriani, Dewi Utami; Ariyanti, Fajar; Zilhadia; Kilic, Bulent (Public Health of Indonesia, 2026)
Background: Iron deficiency anemia (IDA) is a significant public health issue due to its prevalence and numerous contributing factors, specifically among female adolescents. Objective: The study aimed to examine the influence of knowledge and attitude on IDA prevention practice among female adolescents in Bogor City, Indonesia. Methods: This cross-sectional study was carried out among 20 junior high schools in Bogor City, Indonesia. A total of 1.410 female students were selected through a non-probability sampling method. The Spearman rank correlation test was then used to examine the relationship between knowledge, attitude, and practice regarding IDA prevention. Results: The results showed that the average scores for knowledge, attitude, and practice were 5.92 (out of 15), 11.56 (out of 15), and 8.95 (out of 12), respectively. In addition, knowledge had a significant correlation with attitude (p-value = 0.001, r = 0.185), and attitude showed a significant correlation with practice (p-value = 0.005, r = 0.075). Conclusion: The limited understanding of female students concerning IDA may influence their attitude and practice towards its prevention. This indicates that the implementation of diverse strategies is essential to enhance understanding of anemia, thereby improving prevention behavior. Keyword: Anemia, Chronic Diseases, Developing Countries, Female Student, School-Based